ترقية نتائج تعلم مهارة قراءة اللغة العربية بوسائل الكرتونية لطلاب الصف السابع في المدرسة المتوسطة الإسلامية المحمدية ٧ تاكرهارجو - Budi Setiawan; Khoirotun Ni’mah (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2022)
In Arabic there are four language skills, namely listening, speaking, reading and writing. Of the four skills, the researcher focused this research on reading skills. This research is motivated by the lack of student learning outcomes in learning reading skills. Therefore, with the implementation of cartoon-based media, it is hoped that students can be more enthusiastic in participating in learning, and by doing so, student learning outcomes will also increase. This research is a classroom action research with a qualitative approach. Collecting data using observation techniques, interviews, tests, documentation, questionnaires and field notes. The data analysis uses qualitative data analysis techniques which include data collection, reduction, presentation and conclusions. This research was carried out in two cycles of action, each cycle consisting of four stages, namely the action planning stage, the action implementation stage, the observation stage and the reflection stage. From the results of this study, it can be seen that (1) the application of cartoon-based media carried out at MTs Muhammadiyah 07 Takerharjo is considered effective to improve student learning outcomes. (2) and media based on cartoon stories are able to improve student learning outcomes in Arabic reading skills for seventh grade students of MTs Muhammadiyah 07 Takerharjo.